Conteúdo informacional de ratings corporativos: o caso da Repsol-YPF e Petrobras - Broker Bone, Rosemarie (2005)
In the international capital markets, credit ratings are indispensable firm evaluation tool. Rating agencies claim it includes private information. Yet many players have raised doubts about its informational value. They did not forecast corporate and sovereign defaults and overreacted after crises, say critics. In addition, the quasi-duopoly with effectively no entry weakens market discipline that would induce accurate and timely evaluation. We test the informational content of credit ratings, looking at the case of Repsol-YPF Argentina and Petrobras, two large oil companies that are above the sovereign ceiling. Using complementary methods, the results suggest that, in general, credit rating changes not bring new information to the stock market and are predictable with a small set of publicly available information with small error.